Valorización del vástago de plátano (Musa Paradisiaca L.) En la elaboración de polihidroxialcanoatos por fermentación con Ralstonia Eutropha. (2023)
The main objective of the information presented in this document was the chemical analysis of the banana stem (Musa paradisiaca L.) and its valorization as essential biomass for bioprospecting applications by quantifying the sugars present that may be useful for the microorganism inoculation process. producers of polyhydroxyalkanoate (PHA) polyesters on an industrial scale. The choice of the microorganism was made through a bibliographic analysis of the temperature conditions, yield, dry production of polyhydroxyalkanoates, the nutritional needs of the bacterial strains, the pH level and tolerance to compounds that may be toxic generated in the biomass treatments, as well as its possible metabolization in bacteria. The information was represented in a selection matrix composed of three bacterial strains (Ralstonia Eutropha, Pseudomonas Oleovorans and Paracoccus Denitrificans).